CERTAIN QUESTIONS OF THE PROCEDURE OF CONDITIONAL PUNISHMENT - Yedigaryan, Liana (State and Law, 2022)
The subject of the article is the research of the issues related to the procedure of conditional punishment. The article discusses the issue of envisaging conditional punishment as a duty of the court. In addition, the article discusses the question of the expediency discussing the issue of conditional punishment when the punishment is replaced by imprisonment. The suggestions directed at improving the legislative regulation of the procedure of conditional punishment are presented by the author. Proposals on the improvement of the new criminal code of the Republic of Armenia were presented in the work.